Short Term Safety, Immunogenicity, and Reproductive Effects of Combined Vaccination With Anti-GnRH (Gonacon) and Rabies Vaccines in Female Feral Cats - Novak, Shiri; Yakobson, Boris; Sorek, Shir; Morgan, Liat; Tal, Smadar; Nivy, Ran; King, Roni; Jaebker, Lauren; Eckery, Douglas C.; Raz, Tal (Frontiers in Veterinary Science, 2021)
Overpopulation of free-roaming cats is a major problem leading to negative impacts on animal health and welfare, public nuisance, transmission of zoonotic diseases, and well-documented harm to wildlife. Surgical sterilization had failed to provide a practical solution to free-roaming cats’ overpopulation under field conditions; therefore, efficient and safe non-surgical immunocontraception methods are aspired. Rabies is a deadly virus that may infect people and animals. However, the safety and efficacy of combined vaccination with anti-GnRH and rabies vaccines in feral cats, which often suffer from disrupted health conditions and experienced high stress level, has never been studied. Therefore, our objective was to examine the short-term safety and efficacy of anti-GnRH vaccine (Gonacon™), in combination with rabies vaccine in female feral cats. Mature feral female cats were captured and divided into the following groups: (I) GonaconX1-Rabies: queens vaccinated with both Gonacon™ and rabies (n=5); (II) GonaconX2-Rabies: queens vaccinated twice with Gonacon™ (3w apart) and with Rabies (n=4); (III) OVx-Rabies: queens ovariohysterectomized and vaccinated with rabies (n=4); (IV) Intact-Rabies: queens vaccinated against rabies and remained intact (n=3). Comprehensive veterinary examinations and blood tests were performed every 2w for 14w. Data were analyzed by Repeated-Measures-ANOVA or Fisher-Exact-Test. There were neither systemic nor local adverse reactions at the vaccination sites. Blood count (PCV, TS, RBC, HGB, HCT, WBC) and chemistry (Total protein, Total globulin, Albumin, Urea, Creatinine, Creatine kinase, Bilirubin, GGT, ALT, AST) analyses revealed no differences among groups. There were no differences in serum rabies antibodies titers among groups, and queens kept a protective titer (>0.5IU/mL) starting at 2-4 weeks after vaccination. Anti-GnRH antibodies were detected in all Gonacon-vaccinated queens, excluding one queen (GonaconX2-Rabies group). Anti-müllerian hormone serum concentrations reduced significantly after ovariohysterectomy, as well as gradually following vaccination with Gonacon™, but it remained high in intact queens. Evaluation of vaginal cytology and ovarian histology suggested that reproductive cyclicity was suppressed in Gonacon-vaccinated queens. Our results support the conclusion that in the short term, the combined vaccination with Gonacon™ and rabies is safe and effective in female feral cats. However, further long-term studies are warranted to test this immunologic regimen in feral cats.